Proactive and reactive control by the medial frontal cortex - Stuphorn, Veit; Emeric, Erik (Frontiers in Neuroengineering, 2012)
Adaptive behavior requires the ability to flexibly control actions. This can occur either proactively to anticipate task requirements, or reactively in response to sudden changes. Recent work in humans has identified a network of cortical and subcortical brain region that might have an important role in proactive and reactive control. However, due to technical limitations, such as the spatial and temporal resolution of the BOLD signal, human imaging experiments are not able to disambiguate the specific function(s) of these brain regions. These limitations can be overcome through single-unit recordings in non-human primates. In this article, we describe the behavioral and physiological evidence for dual mechanisms of control in response inhibition in the medial frontal cortex of monkeys performing the stop signal or countermanding task.